Polymers of Intrinsic Microporosity Containing [2.2]Paracyclophane Moieties: Synthesis and Gas Sorption Properties - YUE WU (Advanced Functional Materials, 2024)
The unique structure of [2.2]paracyclophane (PCP) with its rigidity, stability, and planar chirality has gained significant attention in polymer and material research. In this work, the incorporation of amino‐functionalized PCPs within polymers of intrinsic microporosity (PIMs) is reported for the first time. Three different PCP‐PIMs were prepared via a Tröger's base formation mechanism, and their structures characterized via solid‐state NMR, MALDI‐TOF, and SEM. Their porosity was evaluated using gas adsorption (N2 and CO2) based on theoretical calculations such as Brunauer–Emmett–Teller (BET), NLDFT pore size distribution (PSD) and ideal IAST CO2/N2 selectivity (15/85), a crucial separation when considering the capture of CO2 from flue gas. The surface areas were found to be between 200–230 m2 g−1 while the selectivity for CO2/N2 ranged from 46 to 70.